An Orally Bioavailable (Mice) Prodrug of Glutathione - Daune L. Crankshaw; Jacquie E. Briggs; Robert Vince; Herbert T. Nagasawa (MDPI AG, 2021)
L-Cysteine-glutathione mixed disulfide (CySSG), a prodrug of glutathione (GSH), was found to be orally bioavailable in mice, and protected mice against a toxic dose of acetaminophen. If oral bioavailability can also be demonstrated in humans, a wide range of applicability for CySSG can be envisioned.